Convergent Findings for Abnormalities of the NF-κB Signaling Pathway in Schizophrenia - Roussos, Panos; Katsel, Pavel; Davis, Kenneth L; Giakoumaki, Stella G; Siever, Larry J; Bitsios, Panos; Haroutunian, Vahram (Neuropsychopharmacology (New York, N.Y.), 2013)
Neurons exhibit a constitutive level of nuclear factor-κB (NF-κB) signaling and this pathway plays a significant role in neurite outgrowth, activity-dependent plasticity, and cognitive function. Transcription factor analysis was performed in a microarray data set profiled in four different brain regions (n=54 comparison group; n=53 schizophrenia (SZ)). An independent postmortem cohort was used for gene expression (n=24 comparison group; n=22 SZ), protein abundance (n=8 comparison group; n=8 SZ), and NF-κB nuclear activity (n=10 comparison group; n=10 SZ) quantification. Expression quantitative trait locus analysis was performed using publicly available data. Prepulse inhibition (PPI) of the acoustic startle reflex was tested in healthy individuals (n=690). Comparison of microarray data showed that NF-κB was among the transcription factors associated with the differential expression of genes in cases vs controls. NF-κB gene and protein levels and nuclear activation were significantly decreased in the superior temporal gyrus of patients with SZ. Upstream NF-κB genes related to translocation were significantly dysregulated in SZ. The gene expression levels of an NF-κB-associated importin (KPNA4: one of the proteins responsible for the translocation of NF-κB to the nucleus) was decreased in SZ and an SNP within the KPNA4 locus was associated with susceptibility to SZ, reduced KPNA4 expression levels and attenuated PPI of the startle reflex in healthy control subjects. These findings implicate abnormalities of the NF-κB signaling pathway in SZ and provide evidence for an additional possible mechanism affecting the translocation of NF-κB signaling to the nucleus.